(untitled) (Pedagogical Horizons, 2024)
This article presents an evaluation study that focuses on domain-specific aspects of blended learning formats in university teaching. As an example, a subject-didactic planning seminar in primary school teaching was empirically accompanied over two waves at the University College of Teacher Education of the Diocese of Linz. Due to the subject-specific blended learning design with included synchronous coaching structure, a qualitative approach was chosen to answer the research questions. The study should first clarify the viable relationship between digital teaching formats and complex tasks so that a subjective learning gain in terms of extended planning skills is perceived by primary school students and individual learning progress is assessed as positive. The data were collected by means of group discussions (nA1=19; nB1=18; nC1=15) and five prestructured focus group interviews (nA2=10; nB2=9; nC2=8; nD2=4; nE2=5). Findings on students’ perceptions regarding the timing of teaching formats, teaching quality and individual skill development are analyzed and discussed. Assessments for future conceptualizations of a meaningfully rhythmic online teaching are given and should be read as impulses to stimulate a progressive discourse on blended learning formats in higher education.